BACKPACKERS IN CHINA-THEIR CHARACTERISTICS ANDTRAVELEXPERIENCES - ARAM SON (Centre For Tourism Planning and Development, 2009)
This study was conducted to identify the characteristics of backpackers and their travel behaviours in China. Specifically, the study sought to explore backpackers' expenditure patterns, activity preference and travel experience while traveling in China. A self-administered questionnaire was used in this study. The results were analysed based on 233 completed questionnaires distributed tobackpackers staying at youth hostels in Xi'an. The research findings confirmed other previous studies on backpackers. It was found that majority of the backpackers in this study were primarily young and European. The results also indicated that respondents are highly motivated by seeking such goals as self-development and novelty and preferred to participate culture-based travel activities. Although respondents were satisfied with travel experiences in China there was room for improvement. The major issues pointed out by respondents were low standard of hygiene and public toilets, unfriendly frontline service employees at restaurants and train stations, and booking train tickets. It is hoped that the findings of this study will contribute to developing promotional strategies for the backpacker market in China.